An assessment of the iPad as a testing platform for distance visual acuity in adults. Issue 6 (19th June 2013) - Black, J M; Jacobs, R J; Phillips, G; Chen, L; Tan, E; Tran, A; Thompson, B
Abstract : Objectives: Visual acuity is a common measurement in general practice, and the advent of new technology such as tablet computers offers a change in the way in which these tests are delivered. The aim of this study was to assess whether measurements of distance visual acuity using LogMAR letter charts displayed on an iPad tablet computer were in agreement with standard clinical tests of visual acuity in adults with normal vision. Design: Blinded, diagnostic test study. Setting: Single centre (University) in Auckland, New Zealand. Participants: University staff and students (n=85). Participants were required to have visual acuity better than 6/60 and wear habitual refractive correction during testing. Participants were excluded if there was any history of ocular pathology. Primary and secondary outcome measures: Visual acuity measured under a number of conditions. Results: The iPad tablet with its glossy screen was highly susceptible to glare resulting in acuity measurements that were significantly poorer (approximately 2 LogMAR lines) than those made using an ETDRS chart and a standard computerised testing system (n=56). However, fitting the iPad with an antiglare screen and positioning the device away from sources creating reflected (veiling) glare resulted in acuity measurements that were equivalent those made using gold standard charts (n=29). Conclusions: Tablet computers are an attractive option for visual acuity measurement due to portability, the ability to randomise letters, automated scoring of acuity and the ability to select from a range of charts. However, these devices are only suitable for use in situations where sources of glare can be eliminated.